Pre-Service Teachers’ Strategies in Solving Absolute Value Equations and Inequalities - Al Jupri; Dian Usdiyana; Sumanang Muhtar Gozali (Education Sciences, 2022)
Many secondary school students have encountered difficulties when dealing with absolute value equations and inequalities. This condition might be brought to higher education, including by pre-service mathematics teachers in teacher training colleges. The difficulties in dealing with absolute value equations and inequalities, which can be observed from solution strategies, indicate the lack of symbol sense. This study aims to investigate strategies that pre-service teachers used while solving absolute value equations and inequalities from the perspective of symbol sense. To investigate this, we conducted a qualitative case study through two written tests followed by interviews involving 36 pre-service mathematics teachers in one of the state universities in Bandung, Indonesia. The results revealed three different solution strategies for solving either absolute value equations or inequalities. Also, difficulties that occurred during the solution processes of equations and inequalities were addressed. We conclude that the symbol sense characteristics are fruitful for interpreting the selection of solution strategies used by pre-service teachers in solving absolute value equations and inequalities.